2009
DOI: 10.1111/j.1476-5381.2008.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin‐54 at high doses acutely induces testicular degeneration in adult male rats via central mechanisms

Abstract: Background and purpose:The kisspeptins are critical regulators of reproduction and a therapeutic target for reproductive disease. Intracerebroventricular (i.c.v.) or peripheral injection of kisspeptin potently stimulates the hypothalamic-pituitary gonadal (HPG) axis via gonadotrophin-releasing hormone (GnRH). However, little is known regarding the effects of kisspeptin administration on testicular function. We investigated the mechanism(s) of kisspeptin-induced testicular degeneration in the rat. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 60 publications
4
30
0
1
Order By: Relevance
“…The difference between sKp-29 and sKp-10 might be related to differences in degradation rate in the body. Indeed, previous studies, including ours, demonstrated that rKp-52 or hKp-54 shows much higher induction of LH release than 33) and suggested that rKp-52 and hKp-54 are more stable than Kp-10. This notion is in line with the current results demonstrating that administration (5 nmol) of two stable GPR54 agonists consisting of five amino acids, FTM080 and FTM145, induced ovulation in musk shrews, but the same dose of sKp-10 or rKp-10 did not.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between sKp-29 and sKp-10 might be related to differences in degradation rate in the body. Indeed, previous studies, including ours, demonstrated that rKp-52 or hKp-54 shows much higher induction of LH release than 33) and suggested that rKp-52 and hKp-54 are more stable than Kp-10. This notion is in line with the current results demonstrating that administration (5 nmol) of two stable GPR54 agonists consisting of five amino acids, FTM080 and FTM145, induced ovulation in musk shrews, but the same dose of sKp-10 or rKp-10 did not.…”
Section: Discussionmentioning
confidence: 99%
“…However, continuous s.c. administration or single high dose of kisspeptin 54 causes testicular degeneration in rats (Thompson et al 2006, Ramzan & Qureshi 2011. Pretreatment with the GnRH receptor antagonist cetrorelix blocks kisspeptin-induced testicular degeneration, suggesting a GnRH-mediated process through acute hyperstimulation of the HPG axis and not a direct effect of kisspeptin on testes (Thompson et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Evidence from animal studies has shown that kisspeptins exhibit pulsatile secretion within the hypothalamus [108] and continuous Kp-10 stimulation leads to desensitisation of kisspeptin receptors as shown by an initial rise in LH levels followed by a rapid drop to baseline levels [118][119][120][121]. But when Kp-10 was given intermittently as twice daily injections it resulted in chronic stimulation of HPG-axis in both rats and monkeys [122,123].…”
Section: Continuous Kisspeptin Exposure Leads To Desensitisationmentioning
confidence: 99%